Pendokumentasian Departemen Maintenance dan Departemen Warehouse & PPIC di PT Charoen Pokphand Indonesia -Feed Processing Balaraja - Yuwono, Ishak; Anne Y A, Debora (Jurnal Titra, 2013)
PT Charoen Pokphand Indonesia Balaraja (PT CPI Balaraja) is one of feed processing companies. PT CPI Balaraja had installed new SAP system, Production Online, and replaced its manual machines into automatics machines. Therefore, the old standard operating procedures are no longer suitable with the current situation. Updating those procedures are a must and this work became purpose of this thesis, particularly in Maintenance Department and Warehouse & PPIC Department. The updating procedures includes SOP (Standard Operational Procedures), WI (Work Instructions), and Forms. In overall, there are 7 SOP, 41 WI, and 12 Forms revision in Maintenance Department. Additionally, thera are 5 SOP, 33 WI, and 33 Forms revision in Warehouse & PPIC Department.